Morphological diversity of fungal reproductive units in the Lower Devonian Rhynie and Windyfield cherts, Scotland: A new species of the genus Windipila - Harper, Carla (My University, 2020)
The Lower Devonian Rhynie and Windyfield cherts from Scotland contain a remarkable diversity of microscopic fungal propagules and reproductive units; however, only relatively few of these fossils are described. One of them is Windipila spinifera, an unusual reproductive unit from the Windyfield chert that consists of a walled spheroid (~ 100 µm in diam.) surrounded by a mantle of interlaced hyphae; prominent spines and otherwise shaped projections, produced by these hyphae, extend out from the mantle. Here, we present W. wimmervoecksii sp. nov., also from Windyfield, which differs from W. spinifera in that the mantle hyphae produce vesicle-like inflations instead of spines. Narrow processes arising from the inflations connect the persistent inner mantle tier with a probably ephemeral outer tier of irregularly inflated hyphae. There is some evidence to suggest that W. wimmervoecksii was a member of the Glomeromycota; however, the precise systematic affinities remain unresolved. This discovery broadens our understanding of the patterns of mantle formation that were present in fungi by the Early Devonian.
PUBLISHED
Keywords: Fossil fungi; Fungal paleodiversity; Hyphal mantle; Glomeromycota; Reproduction; Subtending hypha; Smart & Sustainable Planet; DEVONIAN; FOSSIL; FUNGI; Fossil Fungi; Fossil spores; Fossils; MICROFUNGI; Rhynie chert; Windyfield chert